Is autonomy a universal value of human existence? Scope of autonomy in medical practice: a comparative study between Western medical ethics and Islamic medical ethics - Rathor, Mohammad Yousuf; Mohd Shah, Azarisman Shah; Hasmoni, Mohamed Hadzri (IIUM Press, 2016)
The practice of contemporary medicine has been tremendously influenced by western ideas and it is assumed by many that autonomy is a universal value of human existence. In the World Health Report 2000, the World Health Organization (WHO) considered autonomy a “universal” value of human life against which every health system in the world should be judged. Further in Western bioethics, patient autonomy and self-determination prevails in all sectors of social and personal life, a concept unacceptable to some cultures. In principle, there are challenges to the universal validity of autonomy, individualism and secularism, as most non-Western cultures are proud of their communal relations and spiritualistic ethos and, thereby imposing Western beliefs and practices as aforementioned can have deleterious consequences. Religion lies at the heart of most cultures which influences the practice patterns of medical professionals in both visible and unconscious ways. However, religion is mostly viewed by scientists as mystical and without scientific proof. Herein lies the dilemma, whether medical professionals should respect the cultural and religious beliefs of their patients? In this paper we aim to discuss some of the limitations of patient's autonomy by comparing the process of reasoning in western medical ethics and Islamic medical ethics, in order to examine the possibility and desirability of arriving at a single, unitary and universally acceptable notion of medical ethics. We propose a more flexible viewpoint that accommodates different cultural and religious values in interpreting autonomy and applying it in an increasingly multilingual and multicultural, contemporaneous society in order to provide the highest level of care possible.